Automated dynamic schema generation using knowledge graph - Priyank Kumar Singh; Sami Ur Rehman; Darshan J; Shobha G; Deepamala N (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
On the internet where the number of database developers is increasing with the availability of huge data to be stored and queried. Establishing relations between various schemas and helping the developers by filtering, prioritizing, and suggesting relevant schema is a requirement. Recommendation system plays an important role in searching through a large volume of dynamically generated schemas to provide database developers with personalized schemas and services. Although many methods are already available to solve problems using machine learning, they require more time and data to learn. These problems can be solved using knowledge graphs (KG). This paper investigates building knowledge graphs to recommend schemas.